HEGEMONI KEKUASAAN DALAM NOVEL TERUSLAH BODOH JANGAN PINTAR KARYA TERE LIYE: PERSPEKTIF ANTONIO GRAMSCI DAN RELEVANSINYA SEBAGAI BAHAN AJAR DI SEKOLAH - Rohmah, Atika; Sholeh, Khabib; Daru Santoso, Suryo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the hegemony of power in Tere Liye’s novel Teruslah Bodoh Jangan Pintar and its relevance as teaching material in schools. The research is motivated by the importance of studying hegemony as a form of power relations that operate not only through domination but also through social consent reflected in literary works. The purpose of this study is to describe the forms of power hegemony found in the novel and to explain its relevance as instructional material in schools. The research employs a qualitative descriptive method with a sociological approach to literature and Antonio Gramsci’s theory of hegemony. The data source is the novel Teruslah Bodoh Jangan Pintar by Tere Liye, while the research data consist of narrative and dialogue excerpts that illustrate hegemonic practices. Data were collected using reading and note-taking techniques, and analyzed through content analysis. The findings reveal that power hegemony in the novel is manifested in four forms: cultural hegemony, ideological hegemony, intellectual hegemony, and state hegemony. These forms depict the efforts of dominant groups to maintain power by shaping social consent and collective awareness. Furthermore, the novel is relevant as teaching material because it contains social, cultural, and ideological values that can foster students’ critical thinking, literary appreciation, and understanding of power relations in society.